Oral Squamous Cell Carcinoma in Relation with Depth of Invasion and Lymph Node Metastasis - Sahi, Rajina; Karmacharya, Dilip; Rao, Thungathurthi Sheshagiri (Journal of College of Medical Sciences-Nepal, 2020)
Background: Squamous cell carcinoma of oral cavity has become one of the most common malignancies in Nepal. Neck node involvement is frequently seen in this type of malignancy. Depth of invasion is one of the most important criteria for determining further management of the patient. This study is undertaken to see whether the depth of tumor invasion is a reliable parameter for predicting regional lymph node metastasis. Methods: This retrospective study was done among 85 patients of pathology department of the College of Medical Sciences Teaching Hospital, Bharatpur from May to Oct 2019. Results: This study found that most of the cases of oral squamous cell carcinoma had occurred in old age within 60-70 years of age. The most common site of occurrence for oral squamous cell carcinoma was tongue (60%), followed by lower alveolus (20%). The depth of invasion of 5mm and more was among 89% of the cases while cervical lymph node metastasis was among 53% cases. Most of the cases (60%) were well-differentiated (Grade I). There was no statistical relationship between depth of invasion and lymph node metastasis (p>0.05). Conclusions: The most common site of oral squamous cell carcinoma was tongue. Depth of invasion was not a predictor for lymph node metastasis. Keywords: depth of invasion; lymph node metastasis; oral squamous cell carcinoma; simple compass divider.